Lipophilic Antioxidants in Various Tissues of Selected Malaysian Freshwater Fish - Lokman, Ezarul Faradianna (2006)
The total antioxidant activity in the muscle, liver and intestine of eleven species of Malaysian freshwater fish known as Pangasius polyuranodon, Anabas testudineus, Channa striatus, Clarias batrachus, Labeo rohita, Tilapia mossambica, Leptobarbus hoevenii, Trichogaster pectoralis, Hemibagrus nemurus, Cyprinus carpio carpio and Puntius gonionotus were evaluated using the optimized thiobarbituric acid (TBA) method. The synthetic antioxidant, butylated hydroxytoluene (BHT) was used as positive control. The peroxidation of linoleic acid in the thiobarbituric acid system was markedly inhibited by all the sample extracts compared with the control assay and also showed very low chelating activity with the iron chelator test. This indicated that the tissue samples contained insignificant quantities of iron chelators which would otherwise interfere with the TBA method. All the fish extracts exhibited total antioxidant activity in the order of muscle (61-81%) > liver (51-83%) > intestine (40-70%). Three fish species identified to have high antioxidant activities in the muscle tissue namely Anabas testudineus, Clarias batrachus and Labeo rohita and a iii species with the lowest antioxidant activity, Hemibagrus nemurus were selected for determination of the lipophilic antioxidants using the High Performance Liquid Chromatography (HPLC) analysis. The high antioxidant activities found in the muscle of Anabas testudineus and Labeo rohita were influenced by the presence of relatively high amounts of lipophilic antioxidants namely a-, P-, y-, 6- tocopherols, retinol and coenzyme Qlo. Liver, which was found to have retinol at 0.71 1 + 0.09 to 6.05 + 0.16 pg/g wet weight probably influenced the antioxidant activities obtained. However, the intestine showed the lowest antioxidant activity compared to the other tissues examined. It was found that P-tocopherol (1.31 6 -3.861 pg/g wet weight) was the only lipophilic antioxidant present. The distributions of the various tocopherol homologues, retinol and coenzyme Q homologues in different tissues of Malaysian freshwater fish indicated that these compounds might be independently regulated in each tissue. The difference in the antioxidant activities in the muscle, liver and intestine of different samples in this study may be influenced by the presence of different types of lipophilic antioxidants in each sample. The three potential Malaysian freshwater fish species with high antioxidant activities identified were Anabas testudineus, Clarias batrachus and Labeo rohita. In conclusion, the Malaysian freshwater fish species examined which were found to have high antioxidant activities are recommended as part of the diet as they may be able to protect the human body from free radicals and retard the progress of many chronic diseases. The fish extracts found to have lipophilic antioxidants in this study also can be used as accessible source of -&;MN WfAN A W L m n p u 7 M~A UYSU natural antioxidants to replace synthetic antioxidants, as possible food supplement as well as in pharmaceutical applications.